Acculturation of Mosque and Church in Indonesia: Case Studies from Toraja - Anthonius Michael; Fatimah Husein; Siswanto Masruri (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
The interaction between culture and religion in Toraja brings social changes in various aspects of life. The cultured Toraja society gets new spiritual content, while religion gets new means to introduce the richness of its faith. This study examined the forms of religious and cultural interactions expressed in Toraja’s houses of worship, namely the Great Mosque of Rantepao and the Church of St. Theresia Rantepao, as the object of this research. In this case, two things that became the main study were how the acculturation of Islam and Catholicism in Toraja at the place of worship of the Great Mosque of Rantepao and the Church of St. Theresia Rantepao is as well as the difference between Islamic and Catholic acculturation in the Great Mosque and the Church of St. Theresia Rantepao. The interaction process between religion and Toraja culture has succeeded in forming a distinctive religious society in Toraja society, which carries out spiritual teachings well, but also upholds the cultural values in society. The Great Mosque of Rantepao and the Church of St. Theresia Rantepao are a form of acculturation of religious teachings about houses of worship and architecture of the Toraja society.